2022
DOI: 10.1126/science.abo7896
|View full text |Cite
|
Sign up to set email alerts
|

Shifting mutational constraints in the SARS-CoV-2 receptor-binding domain during viral evolution

Abstract: SARS-CoV-2 has evolved variants with substitutions in the spike receptor-binding domain (RBD) that impact its affinity for ACE2 receptor and recognition by antibodies. These substitutions could also shape future evolution by modulating the effects of mutations at other sites—a phenomenon called epistasis. To investigate this possibility, we performed deep mutational scans to measure the effects on ACE2 binding of all single amino-acid mutations in the Wuhan-Hu-1, Alpha, Beta, Delta, and Eta variant RBDs. Some … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
232
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(312 citation statements)
references
References 63 publications
31
232
0
Order By: Relevance
“…To provide a systematic comparison, we constructed mutational heatmaps for the RBD interface residues in each of the studied Omicron RBD-hACE2 complexes (Figure 7). Consistent with deep mutagenesis experiments [68,96-99], the strongest stability and binding energy hotspots correspond to hydrophobic residues F456, Y489 and Y501 that play a decisive role in binding for all Omicron complexes (Figure 7). Mutational heatmaps clearly showed that all substitutions in these key interfacial positions can incur a consistent and considerable loss in the stability and binding affinity with ACE2.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…To provide a systematic comparison, we constructed mutational heatmaps for the RBD interface residues in each of the studied Omicron RBD-hACE2 complexes (Figure 7). Consistent with deep mutagenesis experiments [68,96-99], the strongest stability and binding energy hotspots correspond to hydrophobic residues F456, Y489 and Y501 that play a decisive role in binding for all Omicron complexes (Figure 7). Mutational heatmaps clearly showed that all substitutions in these key interfacial positions can incur a consistent and considerable loss in the stability and binding affinity with ACE2.…”
Section: Resultssupporting
confidence: 80%
“…The effect of nonadditive, epistatic relationships among RBD mutations was assessed using protein structure modeling by comparing the effects of all single mutants at the RBD-ACE2 interfaces for the Omicron variants, showing that structural constraints on the RBD can curtail the virus evolution for a more complete vaccine and antibody escape [67]. A systematic analysis of the epistatic effects in the S-RBD proteins was undertaken in an illuminating deep mutational scanning study measuring the impacts of all amino acid mutations in the RBD in the Wu-Hu-1, Alpha, Beta, Delta, and Eta variants [68]. This study showed that N501Y causes significant epistatic shifts in the effects of mutations at Q498 as well as RBD residues 446-449 and 491-496 which take place in the absence of any appreciable structural changes between the RBD variants.…”
Section: Introductionmentioning
confidence: 99%
“…The most recently named variant of concern, Omicron, is characterized by the greatest known genetic divergence from the ancestral virus (Wuhan-Hu-1) and consists of several sublineages, including BA.1, BA.2, BA.3, BA.4, and BA.5. BA.1 was first detected in late 2021 and rapidly replaced Delta to become the globally dominant SARS-CoV-2 strain (3,9,11), aided by its high transmissibility and escape from neutralizing antibodies (6,(12)(13)(14)(15)(16)(17)(18). In early March of 2022, BA.2 became the most prevalent SARS-CoV-2 variant globally (19,20) (Fig.…”
mentioning
confidence: 99%
“…In a recent study, Starr et al . ( 2022 ) showed by deep mutational scanning that epistasis – including sign epistasis – is an important important feature of SARS-CoV-2 evolution.…”
Section: Introductionmentioning
confidence: 93%